MEMBENTUK KARAKTER DENGAN AL-QUR’AN, SATU PERSPEKTIF PENDIDIKAN ISLAM - Anasri Anasri (AL-FIKRA, 2018)
The purpose of this study is to obtain a formula for Islamic Education in the perspective of al quran. The results of the study found that Character in an Islamic perspective is nothing but morality. Noble character is the fruit that results from the process of applying sharia (worship and muamalah) which is based on a solid foundation of aqeedah. Like a building, character or morals are the perfection of the building after the foundation and the building are strong. It is impossible for a character or noble character to manifest in someone if he does not have the right aqeedah and sharia. A Muslim who has true aqeedah or faith will surely manifest in attitudes and behaviors in daily life based on his faith. For example, people who have good and true faith in Allah SWT, he will always obey and carry out all His commands and stay away from all His prohibitions. He will always do good and stay away from things that are prohibited (bad). Faith is not only to Allah SWT, but also to angels, books, Apostles and so on will make their attitudes and behavior directed and controlled, so that they will manifest noble character or character. The same thing happened in the case of sharia implementation. All Islamic sharia provisions lead to the realization of noble character or character